Representations are Misrepresentations: The Case of Cover Designs of Banana Yoshimoto’s Kitchen - Furukawa, Hiroko (TTR, 2012)
Megan Backus’s English translation of Kitchen is notable for being both a critical and commercial success. Critics have praised its readability but noted that its translation strategy is foreignizing. Although its cover designs have not been discussed in relation to domestication and foreignization, the strategies are worthy of mention, because they have huge implications for the symbolic representation of marginalized cultures and dominant counterparts.The American publisher Grove Press uses a foreignizing strategy which succeeds in producing an intelligible image of the Oriental novel which at the same time appeals to readers, and the design accelerated the popularity of this novella in the US. In contrast, the first UK edition uses a photograph of a weeping geisha, even though the main character is a young Americanized Japanese woman. Most importantly, there are no geishas anywhere in this story. The cover may seem foreignizing at first glance, but is in fact, obviously domesticating. This design fits the stereotyped mould of what Westerners regard as “a typical Japanese image,” completely unrelated to the content. This paper investigates how Kitchen has been represented in Western countries, with a focus on the cover designs of the translations.